Multiple Batches of Fermentation Promote the Formation of Functional Microbiota in Chinese Miscellaneous-Flavor Baijiu Fermentation - Liu, Pulin; Miao, Lihong (Frontiers in Microbiology, 2020)
Baiyunbian baijiu, the most popular miscellaneous-flavour baijiu in China, has been widely consumed for decades. Similar to many Chinese baijiu, Baiyunbian baijiu is fermented in five successive batches every year. Sensory analysis demonstrated that the raw baijiu obtained from the last two fermentation batches always has better quality than that produced from the former three batches. In this study, the microbial compositions of fungi and bacteria in each fermentation batch were investigated via high-throughput sequencing. The results showed that Bacillus, Virgibacillus, and Lactobacillus dominated the bacterial community in the last two batches, and the most prevalent fungi were Paecilomyces, Saccharomyces, and Zygosaccharomyces. In contrast, large percentages of fungi belonging to Thermomyces, Thermoascus, Monascus, and Issatchenkia and prokaryotes belonging to Acetobacter, Lactobacillus, and Thermoactinomyces were observed in the former three fermentation batches. GC-MS analysis revealed that the fermented grains sampled from the latter two batches contained high concentrations of ethyl lactate, 2,3-butanediol and ethyl caproate, which were mainly generated by co-fermentation of Lactobacillus and yeast. The high acidity of the fermented grains in the fourth and fifth fermentation batches as well as the large contents of ethanol and moisture promoted the formation of the functional microbial community. This study provides insight into factors that influenced the baijiu fermentation and is helpful for developing new fermentation techniques with higher baijiu quality.